Mapping Multi-Site Clinic Workflows to Design Systems-Enabled Interventions. Issue 1 (14th June 2017) - Coronado, Gloria D.; Retecki, Sally; Petrik, Amanda F.; Coury, Jennifer; Aguirre, Josue; Taplin, Stephen H.; Burdick, Tim; Green, Beverly B.
Objective: Variations in processes for different clinics and health systems can dramatically change the way preventive interventions are implemented. We present a method for documenting these variations using workflow diagrams and demonstrate how understanding workflow aided an electronic health record (EHR) embedded colorectal cancer screening intervention. Materials and Methods: We mapped variation in processes for ordering and documenting fecal testing, current colonoscopy, prior colonoscopies, and pathology results. This work was part of a multi-site cluster-randomized pragmatic trial to test a mailed approach to offering fecal testing at 26 safety net clinics (in eight organizations) in Oregon and Northern California. We created clinic-specific workflow diagrams and then distilled them into consolidated diagrams that captured the variations. Results: Clinics had varied practices for storing and using information about colorectal cancer screening. Developing workflow diagrams of key processes enabled clinics to find optimal ways to send fecal test kits to patients due for screening. The workflows informed the rollout of new EHR tools and identified best practices for data capture. Discussion: Diagramming workflows can have great utility when implementing and refining EHR tools for clinical practice, especially when doing so across multiple clinical sites. The process of developing the workflows uncovered successful practice recommendations and revealed limitations and potential effects of a research intervention. Conclusion: Our method of documenting clinical process variation might inform other EHR-powered, multi-site research and can improve data feedback from EHR systems to clinical caregivers.